Hubungan Durasi Terdiagnosis Diabetes Melitus Tipe 2 Dengan Kejadian Kematian Pada Pasien Diabetes Melitus Tipe 2 Dengan Kejadian Kematian Pada Pasien Diabets Melitus Tipe 2 di Rumah Sakit Budi Kemuliaan Kota Batam - Muhamad Azmi Fanany; Andi Ipaljri Saputra; Muhammad Rizky Bafadhal (Lembaga Pengembangan Kinerja Dosen, 2024)
Diabetes Mellitus is a significant problem in global health. In general, it is known to many people around the world because basically diabetes mellitus can be suffered by all groups, both young and old. The aim of this study was to determine the relationship between the duration of diagnosis of type 2 DM and the incidence of death in type 2 DM sufferers at Budi Kemuliaan Hospital, Batam City. The research was carried out by taking medical record data for Type 2 Diabetes Mellitus at Budi Kemuliaan Hospital, Batam City. The data is then processed by computerization. Analysis of the results uses the Chi Square test if the significance value of p is <0.5% or 0.05, then Ho is rejected, meaning there is a relationship between the independent and dependent variables. Vice versa, if p > 0.05 Ho fails to be rejected, it means there is no relationship between the independent variable and the dependent variable. The results of the study showed that there was a relationship between the duration of diagnosis of type 2 diabetes mellitus and the incidence of death in patients with type 2 diabetes mellitus. Based on the results of this study, it can be concluded that the length of time diagnosed with type 2 diabetes mellitus can influence the incidence of death in patients with type 2 diabetes mellitus.